Perendaman Benih Melon Dengan PGPR Pseudomonas sp. dan Bacillus sp. di Dusun Ngadilegi Utara, Kecamatan Pandaan, Kabupaten Pasuruan - Salsabilla Diva Maharani; Panca Ayu Virgirl; Tutus Puspa Valentine; Safira Rizka Lestari (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Ngadilegi Utara Hamlet is one of the hamlets in Plinlahan Village, Pandaan District, Pasuruan Regency which has large potential land for cultivating plants. Farmers in Ngadilegi Hamlet grow many crop commodities, one of which is melons. Melon (Cucumis melo L) is an annual fruit plant originating from the Persian Hot Valley or the Mediterranean region which is the border between West Asia, Europe and Africa. Melon plants are a type of pumpkin plant which is in the same family as watermelon, cantaloupe and cucumber. One effort to increase melon production in North Ngadilegi Hamlet can be done by good development and correct cultivation technology and supported by the use of new technology, namely the use of bacteria contained in PGPR. Soaking seeds with PGPR aims to ensure that the bacteria contained in PGPR are able to colonize the seeds as early as possible. Proper long soaking treatment of seeds can increase plant yields because bacteria will bind to the seed coat and imbibition into the seeds.